Some littoral sea spiders (Arthropoda: Pycnogonida) from Ecuador, with a new species of Anoplodactylus Wilson, 1878 (Phoxichilidiidae) - Bamber, Roger; Takahashi, Yoshie (Zootaxa, 2005)
Five species of pycnogonid from shallow-water sampling of the hyperbenthos on some sandy beaches in Ecuador in 2001 and 2002 are discussed. Three of the species, Tanystylum isthmiacum Stock, 1955, Anoropallene palpida (Hilton, 1939) and Anoplodactylus californicus Hall, 1912, have been recorded previously from Ecuador waters; one species, Ammothella symbia Child, 1979, is newly recorded for Ecuador; one species of Anoplodactylus is described herein as new. The currently known pycnogonid fauna of Ecuador is listed.